STRATEGI MARKETING MELALUI KOMUNIKASI INTERAKTIF LANGSUNG (STUDI KASUS DI PT. ALLIANZ SURABAYA) - Kusumaningrum, Prilga Westrin; Azizah, Nurul (Triwikrama: Jurnal Ilmu Sosial, 2025)
This research aims to analyse the marketing strategy through direct interactive communication implemented at PT Allianz Surabaya. Direct interactive communication is a marketing approach that prioritises personal relationships between companies and potential customers, either through face-to-face, telemarketing, or digital media. The results showed that this strategy was successful in increasing brand awareness and customer loyalty, especially through campaigns that were tailored to the needs of the local market. In addition, the use of digital media supports communication effectiveness by providing faster and more accurate access to information. The research also highlights the importance of training for the marketing team to improve communication and negotiation skills, which are key to the success of this strategy in creating long-term relationships with customers.